User innovation and entrepreneurship: Case studies from rural India - Vanita Yadav; Preeti Goyal (Journal of Innovation and Entrepreneurship, 2015)
Innovation research has abundant literature on technologically advanced innovations and entrepreneurship. However, literature from a rural innovator and entrepreneur perspective is sparse. Therefore, we explore rural user innovation and entrepreneurship in a developing country, India. Using multiple case study research method, we study cases of five rural user innovations in detail. These rural innovators innovated to alleviate the drudgery of their lives and to fulfill their need for a low-cost local solution to a widespread rural problem. They often face a resource void for commercializing their innovations and we find that external actors can play an enabling role in filling this void. The findings of our study help propose a framework for enabling rural innovation and entrepreneurship in developing countries like India. Further, in addition to poverty alleviation, we found that there was a positive social impact on the lives of rural entrepreneurs and their community.
Keywords: 650; User innovation; Entrepreneurship; Rural innovation; Case study; Developing country